PAEDIATRIC PRIMARY HYPERPARATHYROIDISM PRESENTING WITH BILATERAL SLIPPED UPPER FEMORAL EPIPHYSES: A CASE REPORT - Rosland, Muhammad Zafran Amsyar; Morthy, Sasirekha Krisnan; Ong, Jayne AX; Lim, Poi Giok (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Primary hyperparathyroidism (PHPT) is a rare endocrine disorder in children and adolescents with a prevalence of 2–5 in 100,000. PHPT in this age group is often due to single parathyroid adenoma, whereby surgery remains the definitive treatment. Postoperative transient hypocalcemia is a common complication. Nevertheless, severe hungry bone syndrome (HBS) in paediatric is uncommon and is a challenge in the post-operative management of PHPT. CASE A 14-year-old Malay, male presented with trivial falls and subsequently developed bilateral lower limb pain for 2 months, which led to an abnormal, painful gait for 1 week. He also had nausea, intermittent vomiting, abdominal pain, loss of weight and appetite. Biochemical investigations were consistent with primary hyperparathyroidism. He had severe hypercalcemia, hypophosphatemia with elevated alkaline phosphatase and intact parathyroid hormone (iPTH). Pelvic x-ray revealed bilateral slipped upper femoral epiphysis (SUFE) and periosteal bone resorption at the pelvic bones. A neck ultrasound showed a hypoechoic nodule located posterior-inferior to the right lobe of the thyroid gland. A Tc-99m sestamibi parathyroid scan detected an avid lesion inferior to the right thyroid lobe. His severe hypercalcemia was managed by hydration and loop diuretics. For preoperative optimisation, he received intravenous zoledronate and subcutaneous calcitonin. He underwent a right-focused parathyroidectomy and histopathology confirmed the diagnosis of parathyroid adenoma. Post-operatively, he developed severe HBS. He had symptomatic hypocalcemia post-parathyroidectomy for which he required continuous calcium gluconate infusion, calcitriol, calcium carbonate and cholecalciferol. Continuous intravenous calcium and intravenous alfacalcidol were given for four weeks and stopped when serum phosphorus and alkaline phosphatase levels returned to normal limits. CONCLUSION PHPT in children and adolescents often presents with non-specific symptoms leading to a delay in diagnosis. A diagnosis of PHPT should be considered when they present with bone pain or skeletal deformity associated with radiological imaging of osteolytic lesions.